2010
DOI: 10.5251/abjna.2010.1.5.740.747
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tithonia diversifolia (Hemsley) and inorganic fertilizers on maize yield on Alfisols and Ultisols of western Kenya

Abstract: Smallholder maize (Zea mays L.) farmers cannot cope with the high and ever increasing prices of fertilizers, resulting in continuous low grain yield, chronic food shortage and insecurity. Cheaper, sustainable alternatives of improving soil fertility are being sought. The influence of Tithonia diversifolia (Hemsley) A. Gray and fertilizer application on maize yield was studied on N and Pdeficient Alfisols and Ultisols in western Kenya. An on-farm trial, consisting of six treatments: farmer's practice, N (60 kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The resultant product is called Kwasu organic-based fertilizer (KOBF). The choice of tithonia, a roadside weed having vigorous growth habit, as a component in formulating KOBF was based on its availability virtually everywhere and its potential for raising the levels of the major nutrients in soils (Achieng et al, 2010;Jama et al, 2000). This attempt of the Kwara State University Malete (Kwasu) crop scientists was also informed by the general agreement among several researchers that using a mixture of organic and inorganic fertilizers for soil fertility management significantly performs better on growth and yield of crops than using the single fertilizer types alone (Makinde et al, 2001;Sridhar and Adeoye, 2003;Makinde and Ayoola, 2008;Ogunlade et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The resultant product is called Kwasu organic-based fertilizer (KOBF). The choice of tithonia, a roadside weed having vigorous growth habit, as a component in formulating KOBF was based on its availability virtually everywhere and its potential for raising the levels of the major nutrients in soils (Achieng et al, 2010;Jama et al, 2000). This attempt of the Kwara State University Malete (Kwasu) crop scientists was also informed by the general agreement among several researchers that using a mixture of organic and inorganic fertilizers for soil fertility management significantly performs better on growth and yield of crops than using the single fertilizer types alone (Makinde et al, 2001;Sridhar and Adeoye, 2003;Makinde and Ayoola, 2008;Ogunlade et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is native to eastern Mexico and Central America but has a nearly pan tropical distribution as an introduced species (USDA 2011). It has shown great potential in raising the soil fertility in soils depleted in nutrients (Achieng et al 2007). Originating in Mexico; research has shown its potential in benefiting poor African farmers (Jama et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The different spatial arrangements also depicted production opportunities regarding management, socio-economic and biophysical factors that could be utilized to improve maize yields. The high proportion of organic fertilizer used at the near house plots indicated a high nutrient supply and water retention [44]. This can be utilized to increase maize production by improving timely execution of agronomic activities such as land preparation, weed control and use of long duration maize varieties.…”
Section: The Production Opportunities For the Different Spatial Arranmentioning
confidence: 99%